Functional brain changes in vascular cognitive impairment: a whole brain ALE meta-analysis - Zhang, Chunyang; Xue, Mingchen; Zhang, Han; Li, Juan; He, Mingli (Frontiers in Aging Neuroscience, 2025)
BackgroundVascular cognitive impairment (VCI) is a prevalent form of cognitive dysfunction. Resting-state functional magnetic resonance imaging (rs-fMRI) could serve as a potential biomarker for early detection. This study employed activation likelihood estimation (ALE) meta-analysis to investigate specific neural abnormalities in VCI patients.MethodsWe systematically searched PubMed, Embase, and Web of Science for rs-fMRI studies on VCI that reported amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo), or functional connectivity (FC). Sixteen eligible fMRI studies were included in the ALE meta-analysis.ResultsCompared to healthy controls (HCs), VCI patients exhibited the following rs-fMRI alterations. For ALFF, there was an increase in the left anterior cingulate (AC) and left inferior frontal gyrus, possibly a compensatory over - activation. Decreases were seen in regions like the bilateral precuneus and medial frontal gyri (mFG), linked to cognitive deficits. ReHo increased in the left claustrum and insula, suggesting enhanced local synchronization, but decreased in the right sub - gyral region and middle temporal gyru (MTG), which may relate to language issues. FC was enhanced in areas related to complex cognitive processes, yet reduced in regions crucial for memory.ConclusionVCI patients exhibited distinct functional abnormalities in specific brain regions, reflecting their diverse cognitive impairments. These region-specific alterations may serve as potential biomarkers for early diagnosis and targeted intervention in VCI.